Unharmonious Images Conceived by Troubled Minds: Graphic and Literary Caricatures in Heinrich Heine’s French Affairs and French Painters - Vera Faßhauer (Interfaces)
Although the German poet Heinrich Heine, who moved to Paris in 1831, repeatedly declared his commitment to a subjective and politically engaged way of artistic expression, he vehemently professed his dislike of the graphic satires which appeared in La Caricature and represented the “Citizen King” Louis Philippe in the shape of a pear. Nevertheless, Heine’s own accounts of the current French Affairs for the German press exhibit many clear analogies to the seemingly detested satiric drawings: Not only did he use them as an important vehicle of his own political criticism, but he also matched them with his own verbal caricatures of the French monarch and his cabinet. After showing that Heine and the caricaturists did indeed share the same butts and means of criticism, the article analyses both the graphic and verbal strategies and techniques they employed to avoid press censorship.